Oleanane-Type Triterpenoids of Aceriphyllum rossii and Their Diacylglycerol Acyltransferase-Inhibitory Activity - Seo, Jee-Hee; Kim, Mun-Ock; Han, Ah-Reum; Kwon, Eun-Bin; Kang, Myung Ji; Cho, Sungchan; Moon, Dong-Oh; Noh, Jung-Ran; Lee, Chul-Ho; Kim, Young-Soo; Lee, Hyun-Sun (Planta Medica, 2015)
Six known triterpenoid compounds, 3-oxoolean-12-en-27-oic acid (1), gypsogenic acid (2), 3α-hydroxyolean-12-en-27-oic acid (3), 3β-hydroxyolean-12-en-27-oic acid (4), aceriphyllic acid A (5), and oleanolic acid (6), were isolated from the roots of Aceriphyllum rossii. Their chemical structures were determined by comparison with available 1H-NMR and 13C-NMR data on known compounds. All the isolated compounds were evaluated for inhibitory activity against human diacylglycerol acyltransferases 1 and 2. Most of the isolates exhibited a better inhibitory activity against diacylglycerol acyltransferase 2 (IC50: 11.6–44.2 µM) than against diacylglycerol acyltransferase 1 (IC50: 22.7–119.5 µM). In particular, compounds 1 and 5 showed strong inhibition efficacy towards diacylglycerol acyltransferases 1 and 2, and appeared to act competitively against oleoyl-CoA in vitro. The results also indicated that both compounds reduced newly synthesized triacylglycerol in HuTu80 and HepG2 cells. Oral administration of compound 1 significantly reduced postprandial triacylglycerol in mice following an oral lipid challenge. In conclusion, the current study indicates that compound 1 suppresses both de novo triacylglycerol biosynthesis and resynthesis through the inhibition of diacylglycerol acyltransferase activity, and therefore may be a useful agent for treating diseases associated with a high triacylglycerol level.
Keywords: Aceriphyllum rossii; Saxifragaceae; diacylglycerol acyltransferase; triacylglycerol; triterpenoid